Case report of severe maternal hyponatremia complicating preeclampsia. (18th July 2018) - Hinkson, Larry; Armbrust, Robert; Möller, Annika; Henrich, Wolfgang
Abstract: The incidence of preeclampsia associated maternal and neonatal hyponatremia is reportedly rare and can be life threatening in severe cases. The timely diagnosis and careful management requires a multidisciplinary approach between obstetric, neonatal, endocrinology, and intensive care teams. We report firstly, on a case of severe hyponatremia associated with preeclampsia, secondary to inappropriate Anti-Diuretic Hormone secretion, followed by a review of cases over a one year period at our institution.